Precision microbial regulation: Strategies for modulating GIT microbiota for host health - Pei Zhong; Qin Li; Yanmei Zhang; Cheng Guo; Mahmoud M. Abdelsattar; Yanliang Bi (iMetaOmics)
Abstract Recent advancements in analytical techniques have unveiled the spatiotemporal diversity of the gastrointestinal tract (GIT) microbiota and their associations with host well‐being. Despite these insights, the precise regulation of GIT microbiota remains a significant challenge. Currently, microbial regulatory strategies, including fecal microbiota transplantation (FMT), synthetic microbial communities (SynComs), genetically engineered microorganisms (GEMs), phages, and nanomaterials, are increasingly utilized for their precise influence on GIT microbiota. This review emphasizes the necessity for developing targeted regulatory strategies in GIT and provides a comprehensive summary and comparison of these approaches to explore their regulatory potential. We discuss recent advancements in these strategies, focusing on their mechanisms, efficacy, safety considerations, clinical trials, and optimization at the application level. Finally, we highlight support methods for optimizing modulation strategies, including the timing of microbial regulation, the selection of microbial targets, and the importance of monitoring the gastrointestinal environment to guide effective microbial interventions.